Compulsory face mask policies do not affect community mobility in Germany - Roxanne Kovacs; Maurice Dunaiski; Janne Tukiainen (Aboa Centre for Economics (ACE), 2020)
There is currently a heated debate about making face masks compulsory in public spaces to contain COVID-19. A key concern is that such policies could lead to risk compensating behaviour and thereby undermine efforts to maintain social distancing and reduce mobility. We provide first evidence on the impact of compulsory face mask policies on community mobility. We exploit the staggered implementation of policies by German states and measure community mobility using geo-located smartphone data. We find no evidence suggesting that compulsory masking policies affect community mobility in Germany. We can rule out even small increases larger than 0.03 standard deviations.
Keywords: D9; H12; I12; I18; 330; COVID-19; face masks; social distancing; community mobility